Acid sensing ion channel 2: A new potential player in the pathophysiology of multiple sclerosis. (19th February 2019) - Fazia, Teresa; Pastorino, Roberta; Notartomaso, Serena; Busceti, Carla; Imbriglio, Tiziana; Cannella, Milena; Gentilini, Davide; Morani, Gabriele; Ticca, Anna; Bitti, Pierpaolo; Berzuini, Carlo; Dalmay, Tamas; et al.
Abstract: Acid‐sensing ion channels (ASICs) are proton‐gated channels involved in multiple biological functions such as: pain modulation, mechanosensation, neurotransmission, and neurodegeneration. Earlier, we described the genetic association, within the Nuoro population, between Multiple Sclerosis (MS) and rs28936, located in ASIC2 3′UTR. Here we investigated the potential involvement of ASIC2 in MS inflammatory process. We induced experimental autoimmune encephalomyelitis (EAE) in wild‐type (WT), knockout Asic1 −/− and Asic2 −/− mice and observed a significant reduction of clinical score in Asic1 −/− mice and a significant reduction in the clinical score in Asic2 −/− mice in a limited time window (i.e., at days 20–23 after immunization). Immunohistochemistry confirmed the reduction in adaptive immune cell infiltrates in the spinal cord of EAE Asic1 −/− mice. Analysis of mechanical allodynia, showed a significant higher pain threshold in Asic2 −/− mice under physiological conditions, before immunization, as compared to WT mice and Asic1 −/− . A significant reduction in pain threshold was observed in all three strains of mice after immunization. More importantly, analysis of human autoptic brain tissue in MS and control samples showed an increase of ASIC2 mRNA in MS samples. Subsequently, in vitro luciferase reporter gene assays, showed that ASIC2 expression is under possible miRNA regulation, in a rs28936 allele‐specific manner. Taken together, these findings suggest a potential role of ASIC2 in the pathophysiology of MS. Abstract : In our study, we used complementary approaches (i.e., clinical score, pain modulation, immunochemistry, and histology in mice with experimental autoimmune encephalomyelitis, ASIC2 mRNA in human brain tissue, miRNA regulation in vitro ) to characterize ASIC2 contribution in multiple sclerosis (MS). The integration of evidences as emerged by the different experiments suggests a potential role of ASIC2 in the pathophysiology of MS.